The case of Leonid Plyushch - translated from the Russian by Marite Sapiets, Peter Reddaway, and Caryl Emerson ; editor of the Russian ed. Tatyana Khodorovich ; introd. by Peter Reddaway. (Westview Press)
Translation of Istoriia bolezni Leonida Pliushcha.